Digitalisasi Sistem Pengelolaan Proyek: Meningkatkan Kinerja dan Motivasi Kerja Melalui Adopsi Digital yang Optimal pada PT. Techno Multi Utama - Deri Ramadhan; Laura Lahindah (Publikasi Indonesia, 2025)
This study aims to analyze the influence of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) on job satisfaction and work motivation through the mediating role of Digital Adoption (DA). A quantitative approach was employed using a census method involving the entire population of employees within the studied institution. Data collection was conducted through questionnaires, and regression analysis along with mediation testing was performed using SPSS. The results indicate that PU and PEOU significantly influence DA. Furthermore, DA has an impact on job satisfaction and work motivation and is proven to mediate the effect of PU on job satisfaction as well as the effect of PEOU on work motivation. The study also reveals that both job satisfaction and work motivation contribute positively to employee performance. The implications of this research highlight the importance of effective digital adoption as a bridge between technology perceptions and employee work outcomes..